Needs and challenges of college student-parents : basis for an institutional support program - Joaquin, Lolita Rosario (University of Pangasinan : [s.n.], 2020)
Utilizing the descriptive-survey design of research, this study looked into how college students- parents perceived their dual roles, especially how school responsibilities conflict with family responsibilities and what challenges the respondents encountered while managing their dual roles. This study also sought to find out the different coping strategies employed by student-parents as they hurdle the various challenges of their dual roles. The results of the analysis of the data gathered were used to inform the development of an institutional support program to address some of the needs of this particular segment of the college student population. The study found that student-parents are financially challenged and have a great deal of stress caused by the challenges of parenting. They have difficulty balancing their dual roles which are perceived to be in conflict with each other. Family responsibilities leaves little time to do school work, while school work consumes student-parents' energy making them already tired to do housework when they arrive from school. The study also found that student-parents will be able to cope better with the availability of a strong social support system as well as academic and financial support. Qualitative data revealed that the students use a number of resources to cope with their situation: getting emotional support from friends and family. managing time well, getting inspiration from children/family, focusing on the dream or goal of finishing college, and drawing strength from their faith in God. An institutional support program for college student-parents can help address the different school, personal and family needs of this type of students.
Bibliography: pages 204-213.
CHED-La Union
Keywords: College students